On Contraction Properties for Products of Markov Driven Random Matrices - Guivarc'h, Y. (Журнал математической физики, анализа, геометрии, 2008)
We describe contraction properties on pro jective spaces for products of matrices governed by Markov chains which satisfy strong mixing conditions. Assuming that the subgroup generated by the corresponding matrices is "large" we show in particular that the top Lyapunov exponent of their product has multiplicity one and we give an exposition of the related results.